Improving Research Methods Teaching and Learning in Politics and International Relations: A 'Reality Show' Approach. (February 2014) - Ryan, Matt; Saunders, Clare; Rainsford, Emily; Thompson, Emma
Student dissatisfaction with undergraduate research methods courses in politics and international relations is common across the sector. We suggest that methods teaching suffers from an unhealthy disassociation between research in theory – which we call 'method acting' – and research in practice. Our critical interviews with eminent researchers expose the compromises professional researchers make when designing their research. Students appreciate these insights when combined with first-hand research opportunities. We call this approach a 'reality show'. Our analysis based on survey data and students' evaluations of our approach suggests that these aids can provide an effective resource to improve teaching and learning of research methods.